USING VIRTUAL CLASSES, ONLINE LEARNING AND EDUCATIONAL PLATFORMS (E.G. COURSERA, MOODLE) - Shingis Urmanov (Modern American Journals, 2025)
In the context of rapid digitalization of society, online learning is becoming the most important area of modernization of educational systems. Virtual classes, distance learning platforms and online courses are radically changing the forms, content and organization of the educational process. This became especially noticeable during the COVID-19 pandemic, when digital formats became an integral part of the educational reality. Today, learning using platforms such as Moodle, Coursera, Google Classroom, Edmodo is used not only as a temporary alternative to face-to-face education, but also as an independent educational model that meets the requirements of flexibility, accessibility and personalization. Thus, the study of the effectiveness and pedagogical potential of online learning and virtual platforms is scientifically and practically relevant.
Keywords: Online learning, virtual classrooms, educational platforms, Moodle, Coursera, distance education.